Small-scale Spatial Structures of Plant Species: Mechanisms, Implications, and Future Directions - Thi Van, Nguyen; Buu Thach, Le; Thi Lan Thi, Nguyen (Journal of Forestry Science and Technology, 2025)
Small-scale spatial structures of plant communities represent a critical driver of population dynamics, species interactions, and fundamental ecological processes. At localized scales, plants experience biotic and abiotic conditions that often deviate from broader environmental gradients. These conditions are shaped by conspecific and heterospecific neighborhood interactions, which directly influence individual fitness, survival, and regeneration. Small -scale spatial patterns arise from habitat heterogeneity, dispersal limitations, plant-plant facilitation or competition, interactions with biotic agents (e.g., pollinators, herbivores), and stochastic disturbances. Despite their ecological significance, a comprehensive synthesis of the mechanisms driving these spatial structures remains incomplete, hindering their integration into predictive models of community dynamics. This review synthesizes current knowledge to address critical gaps in understanding, focusing on six key determinants of small-scale spatial organization: (1) habitat heterogeneity, (2) plant dispersal mechanisms, (3) intra- and interspecific interactions, (4) biological environment, (5) disturbance regimes, and (6) multifactorial synergies. Additionally, the functional consequences of these spatial patterns are evaluated, particularly their roles in biodiversity maintenance, intraspecific genetic diversity, and ecosystem recovery trajectories. Methodological limitations are critically examined, including scale mismatches in spatial analyses, overreliance on equilibrium assumptions, and insufficient incorporation of plant functional traits. To address these challenges, several research priorities are proposed: (i) integrating small-scale spatial data into macroecological models using hierarchical frameworks, (ii) adopting plant-centric approaches to quantify individual-level interactions, (iii) identifying ecologically relevant spatial scales through gradient analysis, and (iv) employing spatially explicit models (e.g., point-pattern analysis, agent-based simulations) to disentangle stochastic and deterministic drivers. Finally, the translation of insights from small-scale spatial ecology into restoration practices is emphasized, advocating for leveraging pattern-process feedback loops and incorporating spatial heterogeneity into conservation frameworks. This approach aims to bridge the gap between theoretical understanding and practical applications in ecosystem management.